Ectoparasitic mites, ticks (Acari: Trombidiformes, Mesostigmata, Ixodida) and insects (Insecta: Psocodea, Siphonaptera) of ground-dwelling small mammals in the Baltic States. An annotated checklist - Kitrytė, Neringa; Baltrūnaitė, Laima (Zootaxa, 2023)
This paper presents an annotated checklist of 77 species of ectoparasitic mites, ticks (Acari: Trombidiformes, Mesostigmata, Ixodida) and insects (Insecta: Psocodea, Siphonaptera) found on ground-dwelling small mammals in the Baltic States (Estonia, Latvia, Lithuania). Eight species of five genera of chigger mites (Trombidiformes: Trombiculidae), 26 species of eight genera of laelapid mites (Mesostigmata: Laelapidae), six species of two genera of ixodid ticks (Ixodida: Ixodidae), 11 species of three genera of blood-sucking lice (Psocodea: Hoplopleuridae, Pediculidae, Polyplacidae) and 26 species of 15 genera of fleas (Siphonaptera: Ceratophyllidae, Ctenophthalmidae, Hystrichopsyllidae, Pulicidae) were recorded on ground-dwelling small mammals in the Baltic States. Neotrombicula japonica (Tanaka, Kaiwa, Teramura & Kagaya), Neotrombicula vulgaris (Schluger), Miyatrombicula muris (Oudemans), Hoplopleura edentula Fahrenholz and Polyplax hannswrangeli Eichler are recorded for the first time in the Baltic States.